A new surgical technique of the renal artery control during nephrectomy with tumor thrombus removal - Lisovyi, Volodymyr; Shchukin, Dmytro; Khareba, Gennadiy; Garagatiy, Igor; Polyakov, Nikolay; Mozzakov, P. (My University, 2018)
The nephrectomy safety during removal of kidney tumors with intravenous extension mostly depends on control of the renal arterу. But in certain situations control of the renal artery is a very complicated and dangerous stage of the operation due to presence of the venous collaterals and massive size of the tumor thrombus. Search of the renal artery often accompanied the displacement of the renal vein, inferior vena cava or kidney, which can lead to thrombus fragmentation and pulmonary embolism in the presence of fragile or soft tumor thrombus. We present a novel method of control of the renal artery after performing thrombectomy. Our experience has demonstrated the feasibility and safety of a new surgical technique, including anterior ligation of the renal artery after thrombectomy. This approach decreases the blood loss from the venous collaterals during kidney mobilization and reduces the risk of pulmonary embolism.
Keywords: surgical technique; renal artery control; nephrectomy; tumor thrombus removal; complications